Climbers of the Estação Ecológica de Assis, State of São Paulo, Brazil: Floristics and identification keys - Neto, Nicácio Ribeiro [UNESP]; Ronqui, Raquel Aparecida [UNESP]; Seidinger, Letícia Chedid [UNESP]; Udulutsch, Renata Giassi [UNESP] (Pensoft Publishers, 2018)
Climbers are an important life form in the understory and canopy of tropical forests. They are characterised by constant root connection to the ground and use of other species, mainly trees, as support in their search for higher light. In addition, they have an important role in ecological succession in forest clearings, as they are able to develop rapidly in these environments. Climbers can have high species richness in the biomes in which they are present. Since climbers are of little economic importance, they are usually cut down without regard for their contribution to maintenance of biodiversity and to the structure of the forest. Floristic studies of climbers in Brazil are still scarce and more research is needed. The goal of our research was to develop a floristic survey and identification keys for the climbers of the Estação Ecológica de Assis (EEA) in the cerrado biome of São Paulo state, Brazil. Sampling was carried out every two weeks over ten months, along trails and edges of forest within the EEA. Identification keys were built based on vegetative characters. Thirty-two climber species, belonging to 24 genera and 13 families were recorded. The families with the largest number of species were Bignoniaceae (8 species), Malpighiaceae (5), Apocyn-aceae (3) and Smilacaceae (3). The richest genera were Fridericia (4 species), Banisteriopsis (3) and Smilax (3). The number of species recorded for the forest fragment reveals the important role of climbers in the diversity of forested savannahs (cerradões) in the State of São Paulo.
Keywords: Biodiversity; Cerradão; Forested savannah; Liana; Seasonal forest; Vine